Type studies of Cortinarius phaeopygmaeus and C. rusticellus, and a new salicticolous species C. chrysophilus - Kokkonen Katri (Finnish Mycological Society, 2025)
This article deals with the taxonomy of three species belonging to Cortinarius subgenus Telamonia section Flexipedes. The micromorphologies and mostly ITS gene regions were examined from the lectotypes and some syntypes of Cortinarius phaeopygmaeus J. Favre and C. rusticellus J. Favre. Cortinarius phaeopygmaeus appeared to be a previously unrecognized species. Cortinarius rusticellus is reduced to a synonym of C. comatus J. Favre. Its lectotype and protologue agreed with C. comatus. The syntype of C. rusticellus was conspecific with C. lamoureae Bon. Cortinarius chrysophilus is described as new from Salix vegetation on boreal seashores and in the alpine zone. It belongs to the C. cucumisporus complex.